Decision-making processes of venture capital firms – A survey of Finnish venture capital firms - Partanen, Ere (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Venture capital (VC) is a growing industry globally and the success of many startups all around the world is dependent on the ability of receiving VC financing. In the recent years Finland has seen a serious increase in the number of startup entrepreneurs, this means the race for VC financing is heating up, and it is now more important than ever to understand how the venture capitalists make their investment decisions. The objective of this study is to report the current state of the Finnish VC industry. Doing so, the study answers the following research questions: What kinds of VC firms are operating in Finland and what is the extent of their recent activities? What are the processes that Finnish VC firms go through in their investment decisions? What are the criteria that Finnish VC firms emphasize in their decision-making? What valuation methods are Finnish VC firms using to support their investment decisions? The data for the research was gathered by an online questionnaire sent out to the VC firms operating in Finland. The questionnaire was formed to answer the four research questions of this study. The set of questions was based on analysis of prior academic research and reviews of related books. The questions can be framed based on their purposes. The first purpose of the questions was to obtain data on the profiles and recent investment activities of Finnish VC firms. Secondly the aim was to identify the processes VC firms go through in their investment decisions. The third purpose was to recognize the factors that VC firms emphasize in their decision making and lastly, the purpose was to find evidence on how well in line the valuation methods that VC firms use are with the suggested methods in the finance literature and prior research. This study was conducted as an explorative research and the results are discussed and compared to previous results of existing studies and literature. Based on the results the VC firms in Finland are quite recently founded, small and focused in the Nordics. They recognize six stages in their investment decision-making out of which search for investment possibilities, evaluation of proposals and valuation of the startup are the most important ones. The most important criteria in the evaluation of a startup are management skills and experience, entrepreneur personality and the products growth potential and scalability. It seems that there is no “common practice” when it comes to the valuation of a startup. The firms have different approaches to valuations and combining different methods seems to be popular among most of the firms.